Answer:
The answer is vertical translation down 9 units ⇒ answer (d)
Explanation:
* Lets talk about the transformation
- If the function f(x) translated horizontally to the right
by h units, then the new function g(x) = f(x - h)
- If the function f(x) translated horizontally to the left
by h units, then the new function g(x) = f(x + h)
- If the function f(x) translated vertically up
by k units, then the new function g(x) = f(x) + k
- If the function f(x) translated vertically down
by k units, then the new function g(x) = f(x) - k
* Lets study the problem
- The basic function is y = csc(x)
∵ y = csc(x) - 9
- That means the function translated vertically 9 units down
* Vertical translation 9 units down
* Look to the graph
-The red graph is y = csc(x)
- The green graph is y = csc(x) - 9